Perancangan Sistem Informasi Sekolah Dasar Berbasis Website Menggunakan Metode Rapid Application Development - Esya Ardhana, Farhan; Parga Zen, Bita (Jurnal Sistem Informasi Galuh, 2024)
The Ministry of Education, Culture, Research and Technology of the Republic of Indonesia (Kemendikbudristek) of the Republic of Indonesia has encouraged and provided guidance to schools in Indonesia to have websites as part of efforts to increase the transparency and accessibility of educational information. However, the rules regarding the obligation for each school to have a website are different in each region or province, so it is important to check the guidelines issued by the local education office. This research aims to build a school information system website at SD Negeri 1 Pasir Kidul. The school does not yet have a website as directed by the Ministry of Education and Culture. The absence of a website at the school causes the dissemination of information to the community to be hampered, the school's promotion to the community is not good, so an information system website is needed for the school. The school information system website was developed using the Rapid Application Development (RAD) approach. The RAD method was chosen because it is very efficient compared to other methods which require longer research time. Through the RAD method, you can speed up the process of developing an information system website and ensure that the resulting system meets the school's needs. The result of this research is an information system in the form of a website which aims to disseminate information about SD Negeri 1 Pasir Kidul by displaying school information, school galleries, activities at the school, as well as New Student Admissions (PPDB). The website that has been built is tested using the Black Box Testing method. The results of Black Box Testing prove that the SD Negri 1 Website is running according to needs.